Altered threonine tyrosine kinase (TTK) expression is associated with adverse clinical outcomes in breast tumors: An in silico approach (Research, Society and Development, 2023)
The most common and lethal malignancy in women on a global scale remains breast cancer. Threonine tyrosine kinase (TTK) has been shown to be a critical mitotic spindle assembly checkpoint (SAC) molecule, resulting in correct chromosome segregation and maintenance of genomic stability. Therefore, the present study was carried out to evaluate the expression pattern of threonine tyrosine kinase (TTK) in breast cancer and its potential prognostic and predictive value for therapeutic response using bioinformatics tools. Web platforms containing clinical information and cDNA microarray data were selected to perform in silico analyzes of the potential threonine tyrosine kinase (TTK) marker. The threonine tyrosine kinase (TTK) gene was found to be differentially expressed in tumor samples when compared to healthy breast tissue samples (p